2022
DOI: 10.3390/ma15041497
|View full text |Cite
|
Sign up to set email alerts
|

Analytical and Numerical Approaches for the Design of Concrete Structural Elements with Internal BFRP Reinforcement

Abstract: Although basalt fiber-reinforced polymers (BFRPs) have been known for a few decades, new trends such as sustainability and environmental care have provoked intensified research on its structural applications. In construction, BFRPs, as internal reinforcement, have to compete with traditional steel reinforcement products. Because of their high resistance to aggressive environments, BFRPs have emerged as an attractive solution for the infrastructure in coastal zones. In this article, we discuss some aspects of B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…[1] on deep beams reinforced with carbon fiber tensile reinforcement and reactive powder concrete, and the results showed that the cracks on the surfaces of the deep beams reinforced with reactive powder concrete were effectively suppressed. Zhelyazov T. [2] tested the flexural reinforcement of reinforced concrete beams in coastal areas using basalt with basalt fiber-reinforced polymer (BFRPS), and the results showed that, although the modulus of elasticity of BFRP reinforcement was lower than that of structural steel, the increase in loadcarrying capacity increased with pretensioning. Codina A.…”
Section: Introductionmentioning
confidence: 99%
“…[1] on deep beams reinforced with carbon fiber tensile reinforcement and reactive powder concrete, and the results showed that the cracks on the surfaces of the deep beams reinforced with reactive powder concrete were effectively suppressed. Zhelyazov T. [2] tested the flexural reinforcement of reinforced concrete beams in coastal areas using basalt with basalt fiber-reinforced polymer (BFRPS), and the results showed that, although the modulus of elasticity of BFRP reinforcement was lower than that of structural steel, the increase in loadcarrying capacity increased with pretensioning. Codina A.…”
Section: Introductionmentioning
confidence: 99%